(untitled) (American International Journal of Education and Linguistics Research, 2021)
Choosing the best pedagogies and methods for students has become a focal issue in education. Hence, teachers need to evaluate and improve various skills. Therefore, this study was set up to investigate the teachers teaching methods they use during their teaching. The researchers have selected this Hence, teachers need to evaluate and improve various skills. Therefore, this study was set up to investigate the teachers teaching methods they use during their teaching. The researchers have selected this topic because to find out the types of teaching methods and to evaluate that how teachers use the subject and pedagogical knowledge. Currently, there are three Teacher Training Colleges in Paktika province, and the current study is conducted in Zarghun Shahr. The important thing is that how often they use the teaching method theories which they have learned, also at which level they understand their students to be able to identify students and their differences and learning styles. In this study, two mathematics teachers were observed during their teaching. Which were quite important for the current study to observe which methods do teachers use while they teach. The researchers also interviewed both the students who were in those classes and their teachers. The data have been collected by using observation and interview tools. And the unit of this research is teacher educators and students of teacher training colleges. This study will help all teachers (lecturers, teacher educators, and primary and secondary school teachers), to adapt useful methodologies in their classrooms.